2013
DOI: 10.4209/aaqr.2012.07.0179
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Filter Penetration and Quality Factor of Particulate Respirators

Abstract: In the present study, a theoretical model was used to examine factors affecting the filtration characteristics of filters used for respiratory protection. This work was designed to support the particulate filter test requirements established in 1996. The major operating parameters examined in this work include face velocity, fiber diameter, packing density, filter thickness, and fiber charge density. Characteristics of the most penetrating particle size were also modeled with the same operating parameters.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 29 publications
5
105
0
Order By: Relevance
“…5(a) show that the penetration efficiency for charcoal cartridge against NaCl aerosols was increased with the increase of air intake, but decreased with the increase of particle size (less significant). Huang et al (2013) also found that aerosol penetration through filter media increased with increasing face velocity. According to the NIOSH (1996) requirements for P100 filters or the Department of Energy (2015) requirements for HEPA filters, the filtration efficiency against the most penetrating particle size (MPPS) (0.3 µm) should be at least 99.97%.…”
Section: Penetration Efficiency Of Aerosols In Charcoal Cartridgesmentioning
confidence: 84%
“…5(a) show that the penetration efficiency for charcoal cartridge against NaCl aerosols was increased with the increase of air intake, but decreased with the increase of particle size (less significant). Huang et al (2013) also found that aerosol penetration through filter media increased with increasing face velocity. According to the NIOSH (1996) requirements for P100 filters or the Department of Energy (2015) requirements for HEPA filters, the filtration efficiency against the most penetrating particle size (MPPS) (0.3 µm) should be at least 99.97%.…”
Section: Penetration Efficiency Of Aerosols In Charcoal Cartridgesmentioning
confidence: 84%
“…Higher porosity and larger fiber diameter can lead to lower pressure drop, and also negatively impact on the collection efficiency. Therefore, determination of the optimum points among the effecting parameters is so important (Huang et al, 2013). Wang et al (2008) showed that filter efficiency had a negative exponential relationship with the fiber diameter and a positive exponential relationship with solid volume fraction (equal to one minus the porosity), and filter pressure drop had a negative exponential relationship with porosity and fiber diameter (Wang et al, 2008).…”
Section: Determination Of Optimal Conditionsmentioning
confidence: 99%
“…Normally, the lower packing density, higher porosity, thinner filters, and larger fiber diameter can lead to lower pressure drop, whereas all of these properties lead to lower collection efficiency. Therefore, finding the optimum balance between these two factors is very critical (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The filter quality factor (q f ) combines P and ∆p, and is an index of filter media performance (Huang et al, 2013). The term q f is defined as follows.…”
Section: Effects Of Loaded Bacteria On Filter Performancementioning
confidence: 99%